2007
DOI: 10.1080/01443610601124307
|View full text |Cite
|
Sign up to set email alerts
|

Could γ/δ T cells influence the mother's rejection in recurrent aborted embryos?

Abstract: The possibility that the investigation of aborted material may identify aetiologies not easily detectable from even a careful clinical investigation, suggested a study of the T-cell receptors (TCRs) of decidual-infiltrating T-lymphocytes in recurrent spontaneous miscarriage (RSM). From 33 cases of RSM (>3 previous consecutive miscarriages, range 3-5, mean 3.7), PCR products were analysed by 15% acrylamide gel electrophoresis and visualised under UV illumination after ethidium bromide staining. A broad band obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
1
0
0
Order By: Relevance
“…During LIT treatment, immunization with paternal lymphocytes stimulates the maternal immune system and motivates BA production that may contribute to a successful pregnancy. 16 In the present study, we observed that 77.9% of URSA patients became BA positive after LIT and the conversion rate increased along with more LIT. Accordingly, the pregnancy rate extensively ascended after LIT, from 29.6% to 65.3%, and live birth rate significantly grew, from 50.6% to 80.3%.…”
Section: Discussionsupporting
confidence: 53%
“…During LIT treatment, immunization with paternal lymphocytes stimulates the maternal immune system and motivates BA production that may contribute to a successful pregnancy. 16 In the present study, we observed that 77.9% of URSA patients became BA positive after LIT and the conversion rate increased along with more LIT. Accordingly, the pregnancy rate extensively ascended after LIT, from 29.6% to 65.3%, and live birth rate significantly grew, from 50.6% to 80.3%.…”
Section: Discussionsupporting
confidence: 53%